2019
DOI: 10.1007/s12011-019-01983-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Micromineral Distribution Within the Body of Ornamental Fish Species

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science+Business Media, LLC, part of Springer Nature. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to selfarchive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Therefore, the benthic diet of Garra is the likely explanation for the higher accumulation of minerals. The distinct differences in micromineral accretion are in agreement with our observation in a study with ornamental fish kept in similar conditions (Negisho et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the benthic diet of Garra is the likely explanation for the higher accumulation of minerals. The distinct differences in micromineral accretion are in agreement with our observation in a study with ornamental fish kept in similar conditions (Negisho et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, due to increasing population numbers and economic growth, the total demand for fish in Ethiopia is growing. As a result, wild fisheries are over-exploited, specific commercially known fish resources reached their natural limits, and thus led to the decline in stocks of fish of targeted species (Asaminew, 2012;NADSE, 2009). However, the demand for fish consumption is increasing only on the specific tissues (fillet) and a limited number of species (Nile tilapia, African catfish and Nile perch) are frequently consumed.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic functions of minerals are diverse, meaning that their body concentrations can point to particular physiological traits. Bayissa et al (2019) found large differences in micromineral concentrations among fish species, even when kept under identical conditions, showing the divergence in evolutionary adaptations to their original habitats.…”
Section: Introductionmentioning
confidence: 99%